The paleoenvironmental characteristics of the upper Triassic Bagong Formation in the northern Qiangtang basin and its control action on organic matter enrichment - Wang, Rui; Zhang, Shuai; Zhang, Guoqiang; Wu, Xinhe; Song, Jizheng; Pang, Shouji; Yin, Jianguo (Frontiers in Earth Science, 2025)
The Upper Triassic of the Qiangtang Basin is a key strata for oil and gas exploration in the Qinghai-Tibet Plateau. However, it has been controversial argued about the paleoenvironmental control mechanisms for the development of its source rocks. Based on the core samples from Well QK-9, this study reveals the climate and salinity on organic matter accumulation through comprehensive analysis of both organic geochemistry (TOC, Rock-Eval pyrolysis) and inorganic geochemistry (major and trace elements, pyrite content and isotopes). The results are: (1) The middle section consists of relatively good source rocks with relative high TOC (TOC = 0.70%–2.27%, with an average of 1.22%), while the upper and lower sections are poor source rocks for the low TOC (TOC = 0.07%–0.58%, with an average of 0.30%). (2) Paleoclimate (transitioning from humid to arid and back to humid) and paleosalinity (shifting from low to high and then to low) are the primary factors contributing to the vertical differentiation of source rocks. In contrast, the influence of oxidation conditions and biological productivity during that period was relatively minor. (3) In the upper and lower parts of the Bagong Formation, the accumulation of pyrite (with an average of 3.2%) is negatively correlated with low TOC (<0.3%), indicating that the sulfate-reducing bacteria (BSR) exacerbate the degradation of organic matter in a reducing environment. In the middle section, pyrite is less and the TOC increases significantly (with an average of 1.22%). This study reveals the negative correlation between pyrite accumulation and low TOC, challenging the traditional understanding that “reducing environments favor source rock formation” and proposing a “climate-salinity coupling” model for organic matter accumulation as a new theoretical basis for the evaluation of marine source rocks and oil and gas exploration in the complex tectonic background of the plateau.